Organizing activities for students of chemistry pedagogy to research according to the CDIO approach in Vietnam - Giac, Cao Cu; An, Dang Thi Thuan; Hiep, Le Thi Thu; Hoang, Ly Huy; Duc, Nguyen Mau (Journal of Education and e-Learning Research, 2024)
A comprehensive educational framework is provided by the Conceive-Design-Implement-Operate (CDIO) which is particularly relevant to engineering and applied sciences. This paper investigates the application of the CDIO approach in the field of chemistry pedagogy in Vietnam focusing on its adaptability to the current educational demands and its potential to enhance the competency of future teachers. The CDIO approach develops training curricula and output standards based on input from teachers, students, alumni and recruitment firms. This study uses the CDIO approach extensively with professional knowledge, social awareness and creative tendencies. The study involved a survey of 240 chemistry teachers and 242 students from various universities across Vietnam. Data were collected through online surveys using Google Forms and processed using SPSS software for statistical analysis. The research analyzed the alignment of practical teaching activities with CDIO standards and developed a framework for experimental practice competency. Findings indicated a robust implementation of the CDIO approach in chemistry pedagogy. In laboratory safety, experimental planning, execution and competence were high. The study shows that the CDIO strategy enhances professional competence and practical abilities in Vietnamese chemistry pedagogy students. It promotes collaboration and personal growth to meet changing educational needs. The CDIO approach could transform chemistry pedagogy in Vietnam suggesting science education reforms and capacity building.